High-stability lithium-rich lithium ferrite positive electrode lithium supplementing material as well as preparation method and application thereof

Through high-priced metal doping and the coordinated modification of the fluorinated layer and the carbon cladding layer, the shortcomings of lithium-rich lithium-ferrate supplementary materials in air stability and lithium-replenished lithium-ferrate supplementary materials are solved, and the effects of high stability and high lithium-replenished capacity are achieved.

CN120364758APending Publication Date: 2025-07-25安徽得壹能源科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510597361.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-09
Publication Date
2025-07-25

AI Technical Summary

Technical Problem

The existing lithium-rich lithium-ferrate positive electrode lithium supplement materials have shortcomings in air stability and lithium supplement capacity, especially during the crushing process, which produces a large amount of fine powder and interface side reactions, resulting in attenuation of battery capacity.

Method used

The high-valent metal doping and the collaborative modification method of the fluorinated layer and the carbon cladding layer are adopted to reconstruct the crystal structure of the material through high-valent metal cation doping to form a high-bonding M-O bond network, and a fluorine ion is introduced during the sintering process to replace the interface oxygen sites of the material surface to form a stable Fe-F bond and carbon cladding layer to improve the air stability and conductivity of the material.

Benefits of technology

The air storage stability and lithium supplement capacity of the material have been significantly improved. After 24 hours, the pH increase is controlled within 0.1, the increase in the surface residual alkali volume is less than 20 wt%, and the attenuation rate of lithium supplement capacity is less than 2%, breaking through the technical bottleneck that is difficult to achieve both high capacity and low stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120364758A_ABST
    Figure CN120364758A_ABST
Patent Text Reader

Abstract

The invention discloses a high-stability lithium-rich lithium ferrite positive electrode lithium supplementing material as well as a preparation method and application thereof, and belongs to the technical field of lithium ion batteries. The preparation method provided by the invention comprises the following steps: mixing a lithium source, an iron source and an M source, sintering and crushing to obtain a precursor; the M source is a compound containing metal M, and the valence state of the metal M is more than four; the chemical general formula of the precursor is LiaFexM1-xO4, a is more than or equal to 4.5 and less than or equal to 5.5, and x is more than or equal to 0.7 and less than or equal to 1.0; and mixing the precursor, a fluorine source and a carbon source, sintering and crushing. The positive electrode lithium supplementing material prepared by the invention has the advantages that the proportion of nanoscale fine powder is small, the storage stability is obviously improved, after the positive electrode lithium supplementing material is placed in an air environment for 24 hours, the increase amplitude of the pH value is controlled within 0.1, the increase amplitude of the residual alkali amount on the surface is lower than 20wt%, and the positive electrode lithium supplementing material has relatively high lithium supplementing capacity which can reach more than 700mAh / g.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium - ion batteries, and particularly to a high - stability lithium - rich lithium ferrate cathode lithium - supplementing material, a preparation method thereof, and an application thereof. Background Art

[0002] The information disclosed in the background art of the present invention is only intended to increase the understanding of the overall background of the present invention, and is not necessarily regarded as an admission or an indication in any form that this information constitutes the prior art already known to those of ordinary skill in the art.

[0003] During the first charge - discharge process of a lithium - ion battery, the organic electrolyte is reduced and decomposed on the surface of the negative electrode to form a SEI film, consuming a large amount of Li + at the positive electrode, resulting in a low first - cycle efficiency and reducing the battery capacity and energy density. By introducing additional active lithium into the battery cell to make up for the irreversible lithium consumption during the first charge - discharge process, the consumption of active lithium during the cycling process can be slowed down, thereby improving the calendar life and energy density of the battery.

[0004] Currently, pre - lithiumation technologies include negative - electrode lithium - supplementing and positive - electrode lithium - supplementing. Negative - electrode lithium - supplementing is still limited by several major problems in battery manufacturing processes: the use of metallic lithium is incompatible with the production environment, conventional solvents, binders, and heat - treatment processes, etc., making negative - electrode lithium - supplementing a great challenge. Positive - electrode lithium - supplementing mainly involves adding a lithium - supplementing agent to the positive - electrode material. Compared with negative - electrode lithium - supplementing, it is more convenient, and due to its high safety and the need not to change the existing battery production process, it has the most promising industrial application prospects.

[0005] Positive - electrode lithium - supplementing additives mainly focus on lithium - rich compounds. Li2NiO2 and Li5FeO4 have the highest feasibility. Among them, Li2NiO2 has a high cost, and the lithium - supplementing capacity is 250 - 400 mAh / g; Li5FeO4 has a better cost - performance ratio and a higher capacity, and the lithium - supplementing capacity is 600 - 800 mAh / g. However, Li5FeO4 has poor stability in air, and its performance deteriorates rapidly when exposed to air. Moreover, due to its low conductivity, the capacity is low. Secondly, the sintering phenomenon during the synthesis heat - treatment process of Li5FeO4 is very serious. Therefore, the pulverization process is essential. However, a large amount of fine powder is generated during the pulverization process, and various side reactions occur due to the fine powder, resulting in a high residual - lithium growth rate, a large pH change, and also causing battery - capacity attenuation.

[0006] Therefore, how to provide a lithium - rich lithium ferrate cathode lithium - supplementing material with both good storage stability and high lithium - supplementing capacity and a preparation method thereof is an urgent problem to be solved. Summary of the Invention

[0007] In view of this, the present invention provides a high-stability lithium-rich lithium iron phosphate cathode lithium supplement material, a preparation method and an application thereof. The lithium-rich lithium iron phosphate cathode lithium supplement material provided by the present invention can not only exhibit a high lithium supplement capacity, but also significantly reduce the proportion of fine powder, has good air stability and interfacial stability, and good electrical conductivity, and the assembled battery has a low internal resistance.

[0008] In the first aspect, the present invention provides a preparation method of a high-stability lithium-rich lithium iron phosphate cathode lithium supplement material, comprising the following steps: S1. Mix a lithium source, an iron source and an M source, and then sinter and pulverize to obtain a precursor; the M source is a compound containing metal M, and the valence of metal M is above tetravalent; the chemical general formula of the precursor is Li a Fe x M 1-x O4, where 4.5 ≤ a ≤ 5.5 and 0.7 ≤ x ≤ 1.0; S2. Mix the precursor, a fluorine source and a carbon source, and then sinter and pulverize to obtain the high-stability lithium-rich lithium iron phosphate cathode lithium supplement material.

[0009] Preferably, the metal M is selected from one or more of Zr, Ti or W.

[0010] Further, the M source is one or more of an oxide, a nitrate, a sulfate or an oxalate of metal M; the molar ratio of the Fe element in the iron source to the metal M element is (20-200):1.

[0011] Preferably, the lithium source is selected from one or more of lithium oxide, lithium hydroxide, lithium carbonate, lithium nitrate, lithium sulfate or lithium phosphate; the iron source is selected from one or more of ferric oxide, ferroferric oxide, ferrous oxalate, ferrous sulfate or ferrous nitrate.

[0012] Preferably, the sintering process in step S1 is carried out in an oxygen-containing atmosphere, the sintering temperature is 700-800 °C, and the sintering time is 1-8 h.

[0013] Preferably, the fluorine source is selected from one or more of ammonium fluoride, calcium fluoride, sodium fluoride, lithium fluoride or potassium fluoride; the carbon source is selected from one or more of glucose, asphalt, sucrose, starch, resin.

[0014] Preferably, the mass ratio of the fluorine source, the carbon source to the precursor is (0.04-0.3):(1-4):100.

[0015] Preferably, the sintering process in step S2 is carried out in an inert atmosphere, the sintering temperature is 400-800 °C, and the sintering time is 1-8 h.

[0016] In a second aspect, the present invention provides a high-stability lithium-rich lithium ferrite positive electrode lithium replenishing material prepared by the above-mentioned preparation method.

[0017] In a third aspect, the present invention provides the use of the above-mentioned high-stability lithium iron-rich lithium positive electrode lithium supplement material in lithium-ion batteries.

[0018] Compared with the prior art, the present invention has achieved the following beneficial effects: (1) The present invention reconstructs the crystal structure of the material at the atomic scale by introducing high-valent metal cation doping. High-valent metal cations preferentially occupy key sites of the lattice by virtue of strong electrostatic forces, forming a high-bond energy MO bond network, significantly increasing the binding energy of lattice oxygen and inhibiting oxygen loss, thereby enabling the material to exert its optimal lithium replenishment capacity; at the same time, the lattice strengthening effect produced by high-valent ion doping increases the strength of the material particles, reduces the generation of micron-sized fine powder during the pulverization process, and makes the particle size more uniform, significantly improving the material processability and air stability.

[0019] (2) In the present invention, based on the stable lattice framework constructed by high-valent doping, in the sintering step of step S2, fluorine ions selectively replace the oxygen sites on the surface of the material. The strong electronegativity of fluorine causes the Fe-O bond electron cloud to shift toward Fe, reducing the high spin state of the interface Fe-O, and effectively inhibiting the interface side reaction; the fluorinated layer formed simultaneously reduces the pH value and residual alkali content on the surface of the material, thereby improving the interface stability. At the same time, the carbon coating layer formed grows epitaxially on the highly fluorinated surface to form a continuous conductive network, which greatly reduces the resistance of the material powder, and synergizes with the fluorinated layer to improve the interface stability.

[0020] (3) The present invention significantly improves the air storage stability of the material through the synergistic modification of high-valent metal doping, fluoride layer and carbon coating layer: after being placed for 24 hours, the pH value increase is controlled within 0.1, the increase in the amount of residual alkali on the surface is less than 20wt%, and the lithium replenishment capacity decay rate is within 2% after the battery is stored for 24 hours, breaking through the technical bottleneck of traditional lithium replenishment materials that are difficult to achieve both high capacity and low stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] The drawings constituting part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their description are used to explain the present invention and do not constitute an improper limitation of the present invention. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without creative work.

[0022] Figure 1 This is a scanning electron microscope image of the positive electrode lithium supplement material prepared in Example 1 of the present invention; Figure 2 This is a scanning electron microscope image of the positive electrode lithium supplement material prepared in Comparative Example 1 of the present invention. Detailed implementation mode

[0023] It should be noted that the following detailed description is exemplary and is intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those of ordinary skill in the technical field to which the present invention belongs.

[0024] The present invention provides a preparation method for a high-stability lithium-rich lithium iron phosphate cathode lithium supplement material, comprising the following steps: S1. Mix a lithium source, an iron source, and an M source, and then sinter and pulverize to obtain a precursor; the M source is a compound containing metal M, and the valence state of metal M is above tetravalent; the chemical general formula of the precursor is Li a Fe x M 1-x O4, where 4.5 ≤ a ≤ 5.5 and 0.7 ≤ x ≤ 1.0; S2. Mix the precursor, a fluorine source, and a carbon source, and then sinter and pulverize to obtain the high-stability lithium-rich lithium iron phosphate cathode lithium supplement material.

[0025] In the above preparation method of the present invention, first, a lithium source, an iron source, and a high-valence metal M source are mixed and then sintered at high temperature. Through a solid-phase reaction, a precursor with the chemical general formula Li a Fe x M 1-x O4 is formed. Among them, the high-valence metal M (valence state ≥ +4) preferentially occupies the octahedral sites in the crystal lattice by virtue of its strong electrostatic force and large ionic radius, forms a high-bond-energy M-O bond with oxygen, and significantly enhances the mechanical strength and oxygen binding ability of the crystal lattice structure. The precise control of the lithium content (4.5 ≤ a ≤ 5.5) ensures the formation of a lithium-rich phase, provides an adequate lithium source for deintercalation, and at the same time avoids the formation of alkaline compounds due to excessive lithium residue on the surface, thereby optimizing the material capacity and processability.

[0026] In the present invention, the precursor is mixed with a fluorine source and a carbon source and then sintered for the second time. Fluoride ions (F - ) partially replace the oxygen ions on the surface layer of the crystal lattice through a surface substitution reaction to form stable Fe-F bonds, reduce the high-spin state of Fe-O at the interface, and inhibit the side reaction between the electrolyte and the active material. The carbon source pyrolyzes during the sintering process to form a continuous conductive carbon layer, and its graphitized structure provides an electron transport channel, significantly reducing the resistance of the material powder. The synergistic coating of fluorine and carbon forms an Fe-F-C composite interface, which not only passivates the surface to reduce lithium loss but also enhances the electron-ion synergistic transport ability. Through the synergistic modification of high-valence metal doping, fluorination layer, and carbon coating layer, the present invention significantly improves the air storage stability of the material.

[0027] In the present invention, the metal M is selected from one or more of Zr, Ti or W. The above-mentioned metal strengthens the lattice oxygen bond through high-valent metal doping, which can not only exhibit a high lithium compensation capacity, but also increase the strength of the particles, avoid the generation of excessive fine powder during pulverization, and affect the air stability of the material. Further, the M source is one or more of an oxide, nitrate, sulfate or oxalate of the metal M.

[0028] In the present invention, the molar ratio of the Fe element in the iron source to the metal M element is (20~200) : 1, more preferably (40~80) : 1. On the premise of ensuring the capacity, the particle strength is improved by appropriate M doping. The molar ratio of Fe to M balances the number of active sites of Fe and the structural strengthening effect of M, and improves the particle anti-crushing property while maintaining a high capacity.

[0029] In the present invention, the lithium source is selected from one or more of lithium oxide, lithium hydroxide, lithium carbonate, lithium nitrate, lithium sulfate or lithium phosphate; the iron source is selected from one or more of iron(III) oxide, iron(II,III) oxide, ferrous oxalate, ferrous sulfate or ferrous nitrate.

[0030] In the present invention, the sintering process of step S1 is carried out in an oxygen-containing atmosphere, and the volume fraction of oxygen is preferably more than 20%. It can be selected to sinter in an air atmosphere, and the present invention further preferably uses a pure oxygen atmosphere; the sintering temperature is 700~800°C, more preferably 750~800°C, and the sintering time is 1~8 h, more preferably 4~6 h; too low sintering temperature or too short time may lead to insufficient sintering.

[0031] The present invention does not impose special restrictions on the pulverization processes in steps S1 and S2, and common pulverization methods in the art can be used. After the pulverization step of step S2, it also includes steps of sieving and iron removal. The finally obtained particle D50 particle size (the particle size value corresponding to the cumulative particle size distribution reaching 50%) is 5~10 μm, more preferably 7~9 μm. The present invention does not impose special restrictions on the sieving and iron removal steps, and common sieving and iron removal steps in the art can be used. The D1 particle size (the particle size value corresponding to the cumulative particle size distribution reaching 1%) of the high-stability lithium-rich lithium iron phosphate cathode lithium compensation material prepared by the method of the present invention is greater than 3 μm, and the proportion of nano-scale fine powder is low.

[0032] In the present invention, the fluorine source is selected from one or more of ammonium fluoride, calcium fluoride, sodium fluoride, lithium fluoride or potassium fluoride, and further preferably ammonium fluoride, which has low cost and can form a good fluorinated layer coating. The carbon source is selected from one or more of glucose, pitch, sucrose, starch, resin, etc. After carbonization, it forms a continuous conductive network, and those skilled in the art can select specific carbon source types according to needs. In one or more embodiments of the present invention, the carbon source is pitch.

[0033] In the present invention, the mass ratio of the fluorine source, carbon source and precursor is (0.04~0.3) : (1~4) : 100. Excessive fluorine element will lead to capacity loss, while insufficient fluorine element will lead to insufficient interfacial stability. Too little carbon element will result in an overly thin carbon coating layer with poor conductivity, and too much carbon element will lead to an overly thick carbon coating layer, which will hinder the diffusion of lithium ions and have an adverse effect on the capacity.

[0034] In the present invention, the sintering process in step S2 is carried out in an inert atmosphere to avoid oxidation of the carbon source; the inert atmosphere can be one or more of nitrogen or noble gases. The sintering temperature is 400~800°C, more preferably 500~600°C; the sintering time is 1~8h, more preferably 4~6h; sintering under these conditions can make the carbon coating uniform while preventing iron from being reduced.

[0035] The present invention also provides a high-stability lithium-rich lithium iron phosphate cathode lithium supplement material prepared by the above preparation method.

[0036] The present invention also provides the application of the above high-stability lithium-rich lithium iron phosphate cathode lithium supplement material in a lithium-ion battery. When the high-stability lithium-rich lithium iron phosphate cathode lithium supplement material obtained by the present invention is used in a lithium-ion battery, at 25°C and under 0.1C charge-discharge conditions, the first-cycle charging capacity is as high as over 720 mAh / g, and the first-cycle lithium supplement capacity is over 700 mAh / g. Moreover, after being exposed for 24 hours, the increase in pH value is controlled within 0.1, the increase in surface residual alkali amount is less than 20 wt%, and the attenuation rate of the lithium supplement capacity is within 2%, breaking through the technical bottleneck that it is difficult to have both high capacity and low stability in traditional lithium supplement materials.

[0037] The technical solution of the present invention will be further elaborated below in conjunction with specific embodiments. The present invention has no special restrictions on the sources of the reagents used in the following embodiments, and commercially available products well-known to those skilled in the art can be used.

[0038] Example 1 This example provides a preparation method for a high-stability lithium-rich lithium iron phosphate cathode lithium supplement material. In this example, the molar ratio n Li : n (Fe + Zr) is 5:1, and n Fe : n Zr is 49:1.

[0039] S1. Take 1000 g of Fe2O3 (6.26 mol), 955 g of Li2O (31.96 mol) and 31.4 g of ZrO2 (0.255 mol) and add them into a high-speed mixer respectively. After mixing evenly, load the evenly mixed materials into a mullite crucible, place the crucible in a box-type atmosphere furnace, introduce oxygen, heat up to 750 °C and keep it at a constant temperature for 6 h. After the furnace temperature cools down to room temperature, unload the materials, and crush them roughly through a pair-roll equipment to obtain the precursor; S2. Take 1000 g of the precursor, 1.94 g of NH4F and 30 g of pitch and add them into a high-speed mixer respectively. After mixing evenly, load the evenly mixed materials into a mullite crucible, place the crucible in a box-type atmosphere furnace, introduce nitrogen, heat up to 600 °C and keep it at a constant temperature for 6 h. After the furnace temperature cools down to room temperature, unload the materials, crush them finely through airflow crushing, remove iron, and pass through a 250-mesh sieve to prepare the lithium-rich lithium iron oxide lithium supplement material.

[0040] Example 2 This example provides a preparation method of a lithium-rich lithium iron oxide cathode lithium supplement material with high stability. In this example, the molar ratio n Li : n (Fe + Ti) is 5:1, and n Fe : n Ti is 49:1.

[0041] S1. Take 1000 g of Fe2O3 (6.26 mol), 955 g of Li2O (31.96 mol) and 20.4 g of TiO2 (0.255 mol) and add them into a high-speed mixer respectively. After mixing evenly, load the evenly mixed materials into a mullite crucible, place the crucible in a box-type atmosphere furnace, introduce oxygen, heat up to 750 °C and keep it at a constant temperature for 6 h. After the furnace temperature cools down to room temperature, unload the materials, and crush them roughly through a pair-roll equipment to obtain the precursor; S2. Take 1000 g of the precursor, 1.94 g of NH4F and 30 g of pitch and add them into a high-speed mixer respectively. After mixing evenly, load the evenly mixed materials into a mullite crucible, place the crucible in a box-type atmosphere furnace, introduce nitrogen, heat up to 600 °C and keep it at a constant temperature for 6 h. After the furnace temperature cools down to room temperature, unload the materials, crush them finely through airflow crushing, remove iron, and pass through a 250-mesh sieve to prepare the lithium-rich lithium iron oxide lithium supplement material.

[0042] Example 3 This example provides a preparation method of a lithium-rich lithium iron oxide cathode lithium supplement material with high stability. In this example, the molar ratio n Li : n (Fe + W) is 5:1, and n Fe : n W is 49:1.

[0043] S1. Take 1000 g of Fe2O3 (6.26 mol), 955 g of Li2O (31.96 mol) and 59.3 g of WO3 (0.256 mol) and add them into a high-speed mixer respectively. After mixing evenly, load the evenly mixed materials into a mullite crucible, place the crucible in a box-type atmosphere furnace, introduce oxygen, heat up to 750 °C and keep it at a constant temperature for 6 h. After the furnace temperature cools down to room temperature, unload the materials. The unloaded materials are roughly crushed by a pair-roll equipment to obtain a precursor; S2. Take 1000 g of the precursor, 1.94 g of NH4F and 30 g of pitch and add them into a high-speed mixer. After mixing evenly, load the evenly mixed materials into a mullite crucible, place the crucible in a box-type atmosphere furnace, introduce nitrogen, heat up to 600 °C and keep it at a constant temperature for 6 h. After the furnace temperature cools down to room temperature, unload the materials. The unloaded materials are finely crushed by airflow crushing, then the iron is removed, and the materials are passed through a 250-mesh sieve to prepare a lithium-rich lithium iron ferrate lithium supplement material.

[0044] Comparative Example 1 Compared with Example 1, the difference in this comparative example is that ZrO2 is not added. n Li : n Fe is 5:1. The specific steps are as follows: S1. Take 1000 g of Fe2O3 (6.26 mol), 936 g of Li2O (31.34 mol) and add them into a high-speed mixer. After mixing evenly, load the evenly mixed materials into a mullite crucible, place the crucible in a box-type atmosphere furnace, introduce oxygen, heat up to 750 °C and keep it at a constant temperature for 6 h. After the furnace temperature cools down to room temperature, unload the materials. The unloaded materials are roughly crushed by a pair-roll equipment to obtain a precursor; S2. Take 1000 g of the precursor, 1.94 g of NH4F and 30 g of pitch and add them into a high-speed mixer. After mixing evenly, load the evenly mixed materials into a mullite crucible, place the crucible in a box-type atmosphere furnace, introduce nitrogen, heat up to 600 °C and keep it at a constant temperature for 6 h. After the furnace temperature cools down to room temperature, unload the materials. The unloaded materials are finely crushed by airflow crushing, then the iron is removed, and the materials are passed through a 250-mesh sieve to prepare a lithium-rich lithium iron ferrate lithium supplement material.

[0045] Comparative Example 2 Compared with Example 1, the difference in this comparative example is that SrO is used to replace ZrO2. The specific steps are as follows: S1. Take 1000 g of Fe2O3 (6.26 mol), 955 g of Li2O (31.96 mol) and 26.5 g of SrO (0.256 mol) and add them into a high-speed mixer. After mixing evenly, load the evenly mixed materials into a mullite crucible, place the crucible in a box-type atmosphere furnace, introduce oxygen, heat up to 750 °C and keep it at a constant temperature for 6 h. After the furnace temperature cools down to room temperature, unload the materials. The unloaded materials are roughly crushed by a pair-roll equipment to obtain a precursor; S2. Take 1000 g of the precursor, 1.94 g of NH4F and 30 g of pitch and add them to a high-speed mixer. After mixing evenly, load the evenly mixed material into a mullite crucible. Place the crucible in a box-type atmosphere furnace, introduce nitrogen, heat it to 600 °C and keep it at a constant temperature for 6 h. After the furnace temperature cools down to room temperature, unload the material. After passing through airflow crushing for fine crushing, remove iron and pass through a 250-mesh sieve to prepare the lithium-rich lithium ferrate lithium supplement material.

[0046] Comparative Example 3 Compared with Example 1, the difference in this comparative example is that CoO is used to replace ZrO2. The specific steps are as follows: S1. Take 1000 g of Fe2O3 (6.26 mol), 955 g of Li2O (31.96 mol) and 19.1 g of CoO (0.256 mol) and add them to a high-speed mixer. After mixing evenly, load the evenly mixed material into a mullite crucible. Place the crucible in a box-type atmosphere furnace, introduce oxygen, heat it to 750 °C and keep it at a constant temperature for 6 h. After the furnace temperature cools down to room temperature, unload the material. After passing through a pair-roll equipment for coarse crushing, obtain the precursor; S2. Take 1000 g of the precursor, 1.94 g of NH4F and 30 g of pitch and add them to a high-speed mixer. After mixing evenly, load the evenly mixed material into a mullite crucible. Place the crucible in a box-type atmosphere furnace, introduce nitrogen, heat it to 600 °C and keep it at a constant temperature for 6 h. After the furnace temperature cools down to room temperature, unload the material. After passing through airflow crushing for fine crushing, remove iron and pass through a 250-mesh sieve to prepare the lithium-rich lithium ferrate lithium supplement material.

[0047] Comparative Example 4 Compared with Example 1, the difference in this comparative example is that NH4F is not added. The specific steps are as follows: S1. Take 1000 g of Fe2O3 (6.26 mol), 955 g of Li2O (31.96 mol) and 31.4 g of ZrO2 (0.255 mol) and add them to a high-speed mixer respectively. After mixing evenly, load the evenly mixed material into a mullite crucible. Place the crucible in a box-type atmosphere furnace, introduce oxygen, heat it to 750 °C and keep it at a constant temperature for 6 h. After the furnace temperature cools down to room temperature, unload the material. After passing through a pair-roll equipment for coarse crushing, obtain the precursor; S2. Take 1000 g of the precursor and 30 g of pitch and add them to a high-speed mixer. After mixing evenly, load the evenly mixed material into a mullite crucible. Place the crucible in a box-type atmosphere furnace, introduce nitrogen, heat it to 600 °C and keep it at a constant temperature for 6 h. After the furnace temperature cools down to room temperature, unload the material. After passing through airflow crushing for fine crushing, remove iron and pass through a 250-mesh sieve to prepare the lithium-rich lithium ferrate lithium supplement material.

[0048] Comparative Example 5 This comparative example is different from Example 1 in that asphalt is not added in this comparative example. The specific steps are as follows: S1. Take 1000 g of Fe2O3 (6.26 mol), 955 g of Li2O (31.96 mol) and 31.4 g of ZrO2 (0.255 mol) and add them into a high-speed mixer respectively. After mixing evenly, load the evenly mixed materials into a mullite crucible, place the crucible in a box-type atmosphere furnace, introduce oxygen, heat up to 750 °C and keep it at a constant temperature for 6 h. After the furnace temperature cools down to room temperature, unload the materials, and crush them roughly through a pair-roll equipment to obtain a precursor; S2. Take 1000 g of the precursor and 1.94 g of NH4F and add them into a high-speed mixer. After mixing evenly, load the evenly mixed materials into a mullite crucible, place the crucible in a box-type atmosphere furnace, introduce nitrogen, heat up to 600 °C and keep it at a constant temperature for 6 h. After the furnace temperature cools down to room temperature, unload the materials, crush them finely through airflow crushing, remove iron, and pass through a 250-mesh sieve to prepare a lithium-rich lithium ferrite lithium supplement material.

[0049] Test Example 1. Powder property test: ① Particle size: Using a Malvern Mastersizer 3000 particle size tester, based on laser diffraction technology and the measurement of the intensity of scattered light. Specifically, when a beam of laser irradiates on particles, diffraction and scattering phenomena will occur. The intensity of these phenomena is related to the size of the particles. By observing the intensity of this scattered light, the particle size distribution can be estimated using the Fraunhofer diffraction theory and the Mie scattering theory. In the present invention, the term "D1" represents the particle size at the 1% point of the cumulative volume distribution according to the particle size, "D10" represents the particle size at the 10% point of the cumulative volume distribution according to the particle size, "D50" represents the particle size at the 50% point of the cumulative volume distribution according to the particle size, and "D90" represents the particle size at the 90% point of the cumulative volume distribution according to the particle size.

[0050] ② Powder resistance: Weigh 0.6 g of the sample, the inner diameter of the container is 11.8 mm, apply a pressure of 20 Mpa, keep the pressure for 10 s, and read the powder resistance under a pressure of 20 Mpa.

[0051] ③Residual lithium (residual alkali): Weigh 10.000 ± 0.050 g of powder, disperse it in 100 g of deionized water, stir well for 10 min, and filter it with filter paper to obtain a clear aqueous solution containing LiOH and Li2CO3. Prepare 0.1 M HCl solution using concentrated hydrochloric acid. Use 0.1 M HCl as the titrant, MR and BTB as indicators, and perform titration on a potentiometric titrator. According to the indicator or potential change on the potentiometric titrator, accurately find the amount of HCl consumed and record the corresponding volume. Calculate the contents of LiOH and Li2CO3 based on the volume of HCl consumed.

[0052] Table 1 shows the particle sizes and powder resistances of the powders of Examples 1 - 3 and Comparative Examples 1 - 5. It can be seen that the doping of high-valence metals Zr, Ti, and W in Examples 1 - 3 significantly reduces the proportion of nanoscale fine powders, which is beneficial to improving the air stability of the material. Figure 1 This is a scanning electron microscope (SEM) image of the cathode lithium supplement material prepared in Example 1 of the present invention. Figure 2 This is a scanning electron microscope (SEM) image of the cathode lithium supplement material prepared in Comparative Example 1 of the present invention. It can be seen that the particle size of the cathode lithium supplement material in Example 1 is more uniform and the proportion of fine powders is significantly less, while the particle sizes of the material in Comparative Example 1 without Zr doping are uneven and there are many fine powders. The powder resistance significantly decreases after carbon coating, indicating that carbon coating greatly increases the conductivity of the powder.

[0053] Table 1 Particle sizes and powder resistances of the powders of Examples 1 - 3 and Comparative Examples 1 - 5

[0054] To further confirm the air stability of the cathode lithium supplement materials of the examples and comparative examples of the present invention, the residual lithium and pH of the prepared materials were tested at 0 h and after storage in an air environment at 25°C and 40% RH for 24 h. The test data are shown in Table 2.

[0055] Table 2 Residual lithium and pH storage stability data of the cathode lithium supplement materials of Examples 1 - 3 and Comparative Examples 1 - 5

[0056] It can be seen from the comparison between Examples 1-3 and Comparative Examples 1-3 in Table 2 that doping with high-valence metals can keep the residual lithium at a low level, and both the growth rate of residual lithium and the growth rate of pH are lower. After being placed for 24 hours, the increase in pH value is controlled within 0.1. This is mainly because doping with high-valence metals improves the particle size uniformity of the particles, and at the same time significantly reduces the content of nanoscale fine powder, thereby reducing the specific surface area of the particles, decreasing the probability of reaction with air, and further improving the storage stability. It can be seen from the comparison between Examples 1-3 and Comparative Examples 4-5 that coating the surface of the material with a fluorinated layer and a carbon layer can improve the storage stability of the cathode lithium supplement material in air.

[0057] 2. Battery performance test The preparation method and test method of the coin cell are as follows: Mix the conductive agent SP, binder PVDF, and the cathode lithium supplement material of the example or comparative example according to a mass ratio of 1.5:2:96.5 to make a slurry, coat it on the aluminum foil, and place it in a vacuum drying oven for more than 24 hours, with a pressure of -0.1 MPa and a drying temperature of 80 °C. After drying, place it in a glove box for standby. After compacting the dried electrode sheet (it is okay if there is no material falling off), use a punching machine to punch out a circular sheet with a diameter of 11 mm, accurately weigh its mass (accurate to 0.1 mg), wrap it with weighing paper and place it on a watch glass. At the same time, also accurately weigh the mass of the aluminum foil of the same model and size of each electrode sheet to be tested and record it. Place the weighed electrode sheet to be tested in a vacuum oven at 80 °C for baking for more than 12 hours. Start assembly when the concentrations of H2O and O2 in the glove box are both lower than 5 ppm. Place various materials in the battery case in turn, and the placement order is: positive electrode cover → 2 drops of electrolyte → positive electrode sheet → separator → lithium sheet & gasket → 3-4 drops of electrolyte → spring piece → negative electrode cover. Seal the assembled battery with a hydraulic Kejing sealing machine. The voltage range for capacity testing is 2.0~4.2 V, the charge and discharge rate is 0.1 C, and the test temperature is 25 °C. After the coin cell is electrochemically tested at 25 °C and 40% RH, store it for 24 hours and then conduct electrochemical testing under the same conditions. The test results are shown in Table 3.

[0058] Table 3 Electrochemical performance data of coin cells assembled with Examples 1-3 and Comparative Examples 1-5 (unit: mAh / g)

[0059] It can be seen from Table 3 that the battery assembled with the cathode lithium supplement material of the example has excellent initial cycle lithium supplement capacity, which can be as high as 700 mAh / g, and the attenuation rate of lithium supplement capacity after storage for 24 hours is 2%. While the comparative examples without doping with high-valence metals and doping with low-valence metals all show lower lithium supplement capacity; although Comparative Examples 4 and 5 show higher initial cycle lithium supplement capacity, their storage stability is poor.

[0060] The above are only the preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included within the protection scope of the present invention.

Claims

1. A preparation method of a high-stability lithium-rich lithium iron phosphate cathode lithium supplement material, characterized in that, It includes the following steps: S1. Mixing a lithium source, an iron source and an M source, sintering and crushing the mixture to obtain a precursor; the M source is a compound containing metal M, and the valence state of the metal M is tetravalent or higher; the chemical formula of the precursor is Li a Fe x M 1-x O4, where 4.5≤a≤5.5, 0.7≤x≤1.0; S2. Mix the precursor, fluorine source and carbon source, and then sinter and pulverize them to obtain the high-stability lithium-rich lithium iron ferrate cathode lithium supplement material.

2. The preparation method according to claim 1, characterized in that, The metal M is selected from one or more of Zr, Ti or W.

3. The preparation method according to claim 2, wherein The M source is one or more of the oxides, nitrates, sulfates or oxalates of metal M; the molar ratio of the Fe element in the iron source to the metal M element is (20-200):

1.

4. The preparation method according to claim 1, characterized in that, The lithium source is selected from one or more of lithium oxide, lithium hydroxide, lithium carbonate, lithium nitrate, lithium sulfate or lithium phosphate; the iron source is selected from one or more of iron(III) oxide, iron(II,III) oxide, ferrous oxalate, ferrous sulfate or ferrous nitrate.

5. The preparation method according to claim 1, characterized in that, The sintering process in step S1 is carried out in an oxygen-containing atmosphere, the sintering temperature is 700-800 °C, and the sintering time is 1-8 h.

6. The preparation method according to claim 1, characterized in that The fluorine source is selected from one or more of ammonium fluoride, calcium fluoride, sodium fluoride, lithium fluoride or potassium fluoride; the carbon source is selected from one or more of glucose, asphalt, sucrose, starch or resin.

7. The preparation method according to claim 1, characterized in that, The mass ratio of the fluorine source, carbon source to the precursor is (0.04-0.3):(1-4):

100.

8. The preparation method according to claim 1, characterized in that, The sintering process in step S2 is carried out in an inert atmosphere, the sintering temperature is 400-800 °C, and the sintering time is 1-8 h.

9. The high-stability lithium-rich lithium iron ferrate cathode lithium supplement material prepared by the preparation method according to any one of claims 1-8.

10. Application of the high-stability lithium-rich lithium iron ferrate cathode lithium supplement material according to claim 9 in a lithium-ion battery.